Evaluation of Vegan and Vegetarian Customers’ Reviews Within the Scope of Expectancy-Disconfirmation Model - CETIN GURKAN, Güney; ÖZYURT, Basak; CELILOGLU AYLAN, Kübra (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2025)
As the concept of veganism continues to gain more attention worldwide, it becomes inevitable for tourist destinations to appeal to vegan travelers. Therefore, the aim of this study is to determine whether Antalya, a renowned tourist destination, is suitable for vegan tourists. In this regard, comments posted on social media formed the basis of the research data, and these data were analyzed based on the Expectancy-Disconfirmation Model, evaluating their conformity to the model. The results revealed that 87.5% of vegan tourists visiting the region had their expectations met, while only 12.5% experienced dissatisfaction. Among those expressing satisfaction, 46% also mentioned their intention to recommend and revisit. A small portion of those dissatisfied expressed they would not revisit, and a few have cautioned other vegans not to visit. Some tourists primarily appreciated friendly staff and quality service, along with a positive atmosphere, favorable location, and reasonable prices. Despite being relatively rare compared to positive aspects, notable negative features include unfriendly staff, poor service, shortcomings in labeling vegan foods, and staff with limited proficiency in English.